The Association between Radiologic Severity of Rotator Cuff Pathology and Supraspinatus Weakness on Biomechanical Assessment (229). Issue 10 (31st October 2021) - Gillinov, Stephen; Varady, Nathan; Abraham, Paul; Kucharik, Michael; Martin, Scott
Objectives: Many different magnetic resonance imaging (MRI)-based classifications are used to characterize rotator cuff supraspinatus pathology, ranging from mild tendinopathy to full-thickness tears. While MRIs are chiefly utilized to guide the need for and approach to operative management of supraspinatus pathology, the functional implications, if any, across the entire range of pathologies have not been defined. The purpose of this biomechanical study was to examine shoulder strength and function in patients presenting with presumptive supraspinatus pathology and to determine if these clinical parameters are correlated with radiologic severity. Methods: We prospectively enrolled 171 patients with suspected rotator cuff pathology disease and without apparent strength deficit on traditional rotator cuff physical examination (PE). Exclusion criteria were radiographically apparent glenohumeral OA, previously diagnosed rotator cuff tear of the affected shoulder, previously diagnosed adhesive capsulitis, prior ipsilateral shoulder surgery, injury to the ipsilateral hand or wrist, limited range of motion, and history or radiographic evidence of anterior or posterior shoulder dislocation. For both clinical (e.g. testing isotonic strength in patients with frank weakness yields unreliable strength measurements and provides little useful information) and ethical (e.g. to avoid causing pain to patients already experiencing significant shoulder pain) reasons, this study evaluating dynamic strength testing was strictly limited to patients with negative traditional, static PE tests. All patients underwent two bilateral shoulder strength tests using dynamometry; first, isometric strength was measured at 90 degrees of abduction and, second, isotonic strength was measured eccentrically from full abduction throughout the full range of motion until the arm was at the patient's side. For both of these tests, the examiner placed the handheld dynamometer (Hoggan microFET® 3; Hoggan Scientific, LLC, Salt Lake City UT, USA) on the patient's wrist, perpendicular to the arm, to measure the force applied along the arc. Absolute strength and symptomatic-to-asymptomatic arm (S/A) strength ratios were calculated. All patients were included in analyses of absolute strength measurements on strength testing; patients who had a history or clinical evidence of contralateral shoulder pathology were excluded from analyses of S/A strength ratios. Patients then underwent shoulder MRI, classifying supraspinatus findings into one of seven ordinal categories. The primary outcome was the relationship between the radiologic severity of supraspinatus pathology on MRI and the degree of rotator cuff strength deficit upon exam. Results were analyzed for both isotonic and isometric function. Results: The study cohort consisted of 171 patients (102 [59.6%] males, 69 [40.4%] females). The mean patient age (± 95% CI) was 52.0 ± 1.9 years. The mean symptom duration (± 95% CI) was 10.8 ± 2.9 months. MRI revealed: 26 (15.2%) instances of no supraspinatus pathology, 37 (21.6%) instances of tendinopathy, 17 (9.9%) instances of supraspinatus fraying, 39 (22.8%) partial thickness tears (PTTs), 13 (7.6%) high-grade PTTs, 12 (7.0%) focal full thickness tears (FTTs)/full-thickness perforations, and 27 (15.8%) FTTs. Isotonic strength : Increasing imaging severity was significantly associated with decreasing absolute strength during isotonic testing ( P =0.036, Table 1 ). Specifically, absolute strength measurements declined with increasingly severe imaging findings, from no tear [59.9 N], to tendinopathy [50.9 N], to fraying [48.2 N], to PTT [55.0 N], to high-grade PTT [48.9 N], to focal FTT/full thickness perforation [45.7 N], to FTT [44.2 N]. Similarly, increasing imaging severity was significantly associated with decreasing S/A strength ratios during isotonic testing ( P =0.022, Table 1). Isotonic S/A strength ratios declined with increasingly severe imaging findings, from no tear [91.9%], to tendinopathy [70.8%], to fraying [66.1%], to PTT [76.2%], to high-grade PTT [75.7%], to focal FTT/full thickness perforation [65.2%], to FTT [63.3%]. Isometric strength : In contrast to isotonic testing, increasing imaging severity was not significantly associated with decreased absolute strength measurements on isometric testing ( P =0.12, Table 2 ). Similar results were seen for isometric S/A ratio, as increasing imaging severity was not significantly associated with S/A strength ratio ( P =0.085, Table 2 ). Conclusions: Radiologic severity of supraspinatus pathology was correlated with dynamic clinical function across the full range of pathology, revealing the functional importance of these frequently-used classifications. The lower discriminatory ability of isometric measurements and higher strength measurements on isometric assessment may be related to a greater role of compensatory musculature in static testing. These biomechanical results support the need for future work investigating the utility of dynamic rotator cuff physical examination maneuvers.